URGENSI PRINSIP NON-DISKRIMINASI DALAM REGULASI UNTUK PENGARUS-UTAMAAN KESETARAAN GENDER - Hamidah, Anisatul (Jurnal Hukum & Pembangunan, 2021)
Discrimination against women seems to have become part of the human history and development because it has happened since years ago until now.Therefore,the issue of discrimination against women is still interesting and becomes an important topic to discuss both at the global level and in Indonesia. Efforts to minimize the existence of discrimination against women have actually been carried outby establishing global consensus listed in various legal instruments such as the Universal Declaration of Human Rights (UDHR) and the Convention on the Elimination of All Forms of Discrimination against Women (CEDAW). These instruments explicitly state the obligation of countries to apply the principle of non-discrimination and equal rights for all people including women. Yet, discrimination against women continues to occur after the global consensus was established more than five decade ago. In many countries, discrimination against women does not only occur as part of cultural and religious traditions but it is alsowritten in regulations. Indonesia as the main focus of this study is one best example in which women face discrimination in many sectors.